1987
DOI: 10.1073/pnas.84.13.4636
|View full text |Cite
|
Sign up to set email alerts
|

Absence of serum growth hormone binding protein in patients with growth hormone receptor deficiency (Laron dwarfism).

Abstract: It has recently been recognized that human serum contains a protein that specifically binds human growth hormone (hGH). This protein has the same restricted specificity for hGH as the membrane-bound GH receptor. To determine whether the GH-binding protein is a derivative of, or otherwise related to, the GH receptor, we have examined the serum of three patients with Laron-type dwarfism, a condition in which GH refractoriness has been attributed to a defect in the GH receptor. The binding of 1251-labeled hGH inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
2
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(68 citation statements)
references
References 22 publications
4
59
2
3
Order By: Relevance
“…Direct evidence of a GH receptor (GHR) abnormality was provided by Eshet et al (3), who demonstrated that hepatic microsomes obtained from two patients failed to bind radiolabeled GH. Subsequent studies indicated that serum concentrations of GH binding protein (GHBP), the extracellular domain of the GHR, were reduced in patients, consistent with an underlying receptor defect (4).…”
mentioning
confidence: 99%
“…Direct evidence of a GH receptor (GHR) abnormality was provided by Eshet et al (3), who demonstrated that hepatic microsomes obtained from two patients failed to bind radiolabeled GH. Subsequent studies indicated that serum concentrations of GH binding protein (GHBP), the extracellular domain of the GHR, were reduced in patients, consistent with an underlying receptor defect (4).…”
mentioning
confidence: 99%
“…In most cases, GH binding activity of binding protein (BP)/receptor is undetectable and this is consistent with a defect in the extracellular domain of the GHR, which results in impaired hormone binding (Daughaday & Trivedi 1987). However, recent reports have described patients with positive GHBP (Buchanan et al 1991, Savage et al 1993.…”
Section: Introductionmentioning
confidence: 83%
“…There was no gross structural abnormality of the circulating growth hormone molecule as probed by radioreceptor and monoclonal antibody assays (47,48). No child had absent growth hormone receptors as assessed by assaying circulating growth hormone binding protein levels (49). Each subject's cultured fibroblasts were normally sensitive to IGF-I with regard to uptake of aminoisobutyric acid (55).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma growth hormone concentrations were quantified by conventional polyclonal RIA, by IM-9 lymphocyte (47) or human liver radioreceptor assay (48), and by two-site monoclonal IRMA (Hybridtech, San Diego, CA). Serum growth hormone binding protein (49) and circulating IGF-I concentration (50) were measured as described previously. Osteocalcin was measured by specific RIA using a commercial antibody (Incstar Corp., Stillwater, MN).…”
mentioning
confidence: 99%